Analisis Tingkat Pengangguran Terbuka, Human Capital Dan Jumlah Penduduk Terhadap Kemiskinan di Sumatera Utara - Marito, Cinta; Nisa, Fadila; Pardede, Nova Novita; Erza, Datuk Sazli Daffa Yudha; Sinaga, Defrin; Hidayat, Nasrullah; Suharianto, Joko (Jurnal Dinamika Sosial Budaya, 2023)
This research aims to find out how much influence the unemployment rate, human capital and population have on poverty in the 2018-2022 period. This research uses quantitative methods with descriptive analysis. The data used in this research is secondary data sourced from the Central Statistics Agency (BPS) of North Sumatra for 4 years from 2018-2022. The data analysis technique uses Random Effect based on the results of the Lagrange Multiplier test. The results of this research show that (1) the independent variables, namely open unemployment, human capital, and population have a significant effect on poverty in North Sumatra province, (2) the level of open unemployment and population have a positive effect and have a significant influence on poverty in North Sumatra, and (3) the Human Capital variable has a negative effect and has a significant influence on poverty in North Sumatra.